Wpływ alternatywnych sposobów rozwiązywania sporów na efektywność ochrony prawnej - Świrgoń - Skok, Renata; Arkuszewska, Aneta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Even though it has not been explicitly articulated in the treaties, the principle of effectiveness plays an important role in the EU system of legal protection. The problem of their effectiveness may, obviously, be examined at the stage of creating the laws, yet this study focuses on selected aspects of effective protection of subjective rights. Private law cases may be handled not only by national judicial bodies, but also by courts of arbitration appointed for the purpose by the will of the parties involved. This is enabled by the principle of party autonomy, fundamental under private law, which in proceedings under civil law is expressed e.g. by the parties’ freedom to decide whether they will turn for protection to national court of law or will pursue their claims otherwise. Hence, in addition to its function as a body resolving disputes by means of adjudication, court of arbitration should settle the matters with the interested parties so that it becomes possible to reconcile differences between them, or at least to prevent further estrangement. Given the above, it is particularly important to ensure efficiency and effectiveness of proceedings held before courts of conciliation and to look at these issues in a broader context of civil proceedings. This mainly results from the fact that although arbitration system is not part of national jurisdiction, by acting in place of national courts of justice and providing legal protection, courts of arbitration perform tasks designated to the state, therefore their operation is sanctioned by the state. Consequently, numerous problems related to the course of proceeding before common courts of law can also be identified in arbitration procedures, even though the latter, having more flexibility, may apply a wider range of means to avoid the inefficiency and lack of effectiveness in their operations. It is obviously difficult to explicitly decide whether or not arbitration proceeding is effective as this depends on a number of factors, such as the composition of the arbitration court and nature of the specific case. Another matter of importance is the competence of the arbitration body in handling claims in civil proceedings. On the one hand it is important to define and apply optimum procedures in examining such cases under arbitration proceeding (to ensure rapid and fair settlement). Any related deficiencies, despite professional expertise of the arbiters, will be an impediment to effective legal protection for the party bringing their claim to arbitration court. On the other hand, it is crucial that the adjudicating panel applies adequate approach to the relevant matter, aiming at its amicable resolution and acting with due diligence. This was already the case in Roman law, because Roman legal concepts creatively adapted to the needs of the successive generations, are also applicable to challenges of the modern civil proceeding. This also relates to the need to ensure access to jurisdiction and to enforce the right of effective civil law procedure.